MENINGKATKAN KEMAMPUAN MENULIS TEKS NARASI MELALUI PEMBELAJARAN BERDIFERENSIASI MENGGUNAKAN MODEL PROJECT BASED LEARNING PADA SEKOLAH DASAR - Trihastuti, Nunuk; Hadi, Panji Kuncoro; Soleh, Dwi Rohman (Universitas PGRI Madiun, 2024)
This research aimed to improve fourth-graders' narrative writing skills through a differentiated project-based learning model. A classroom action research involving teachers and 13 students was conducted. Data was collected through interviews, observations, writing tests, and documents. Results showed significant improvement in writing skills after two cycles. Eighty-five percent of students achieved scores above the minimum criteria. The project-based learning model effectively enhanced students' writing abilities.